The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1073/pnas.93.18.9488
|View full text |Cite
|
Sign up to set email alerts
|

The yeast GAL11 protein binds to the transcription factor IIE through GAL11 regions essential for its in vivo function.

Abstract: The GALlJ gene encodes an auxiliary transcription factor required for full expression of many genes in yeast. The GALI-encoded protein (Galllp) has recently been shown to copurify with the holoenzyme of RNA polymerase II. Here we report that Galllp stimulates basal transcription in a reconstituted transcription system composed of recombinant or highly purified transcription factors, TFIIB, TFIIE, TFIIF, TFIIH, and TATA box-binding protein and core RNA polymerase II. We further demonstrate that each of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 34 publications
4
44
1
Order By: Relevance
“…It has been reported that the holoenzyme of RNA polymerase II, in which Gall lp is a component, enhances basal as well as activated transcription in a reconstituted transcription system [3,4,17,18]. Our recent experiments indicated that Gall lp directly interacts with TFIIE, and further suggested that it is through this interaction that Galllp regulates the promoter activity [19]. We may therefore suggest that Gall lp in the holoenzyme regulates transcription depending on the presence of the TATA box through interaction with TFIIE.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It has been reported that the holoenzyme of RNA polymerase II, in which Gall lp is a component, enhances basal as well as activated transcription in a reconstituted transcription system [3,4,17,18]. Our recent experiments indicated that Gall lp directly interacts with TFIIE, and further suggested that it is through this interaction that Galllp regulates the promoter activity [19]. We may therefore suggest that Gall lp in the holoenzyme regulates transcription depending on the presence of the TATA box through interaction with TFIIE.…”
Section: Discussionmentioning
confidence: 74%
“…This notion has been supported by the recent finding that Galllp copurifies with the RNA polymerase II holoenzyme [17,18]. In fact, immunoprecipitation experiments with antiGall lp antibody have demonstrated that Gall lp coprecipitates with the largest subunit of RNA polymerase II [19].…”
Section: Introductionmentioning
confidence: 80%
“…Related with this idea, it has been reported that in yeast, recruitment of general transcription factors such as TBP, TFIIB, and TFIIH to active promoters requires the function of Mediator (17,25,32). Also, TFIIE interacts with the Mediator protein Gal11 (34). Further analyses will be required to clarify whether these interactions, observed both in yeast and Drosophila, participate in the control of the stepwise preinitiation complex assembly in the course of transcription activation or simply reflect the affinities between the components of preassembled Pol II holoenzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Gal11 residues 866-929 (lines 9 and 10) had an effect equivalent to total deletion of Gal11 (lines 3 and 4). This part of Gal11 (i.e., residues 866-929) is required for whatever general role it plays in the mediator (31). These results, taken together, suggest that LexAϩP201 contacts Gal11 somewhere in the segment encompassed by residues 187-618.…”
Section: Resultsmentioning
confidence: 78%